Optimalisasi Keselamatan Pasien di Post-Anesthesia Care Unit - Widodo, Untung; Wisudarti, Calcarina Fitriani Retno; Krispratama, Avian (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Post-Anesthesia Care Unit (PACU) is a place for monitoring patients who have undergone the anesthesia process, both regional and general. The recovery period begins immediately after the patient leaves the operating table. Complications can occur at any time, including when transferring a patient from the operating room to the recovery room. The patient must be closely monitored and monitored. Several post-anesthesia complications include consciousness disorder, a decrease of peripheral resistance and cardiac output due to residual anesthesia, and hypovolemia due to inadequate fluid replacement during surgery or continued postoperative bleeding. Hypertension may occur due to increased activity of sympathoadrenal and severe pain.